Dietary digestible carbohydrates are associated with higher prevalence of asthma in humans and with aggravated lung allergic inflammation in mice - Musiol, Stephanie; Harris, Carla P; Karlina, Ruth; Gostner, Johanna M; Rathkolb, Birgit; Schnautz, Benjamin; Schneider, Evelyn; Mair, Lisa; Vergara, Ernesto Elorduy; Flexeder, Claudia; Koletzko, Sibylle; Bauer, Carl-Peter; et al. (Allergy, 2023)
BACKGROUND: Dietary carbohydrates and fats are intrinsically correlated within the habitual diet. We aimed to disentangle the associations of starch and sucrose from those of fat, in relation to allergic sensitization, asthma and rhinoconjuctivitis prevalence in humans, and to investigate underlying mechanisms using murine models. METHODS: Epidemiological data from participants of two German birth cohorts (age 15) were used in logistic regression analyses testing cross-sectional associations of starch and sucrose (and their main dietary sources) with aeroallergen sensitization, asthma and rhinoconjunctivitis, adjusting for correlated fats (saturated, monounsaturated, omega-6 and omega-3 polyunsaturated) and other covariates. For mechanistic insights, murine models of aeroallergen-induced allergic airway inflammation (AAI) fed with a low-fat-high-sucrose or -high-starch versus a high-fat diet were used to characterize and quantify disease development. Metabolic and physiologic parameters were used to track outcomes of dietary interventions and cellular and molecular responses to monitor the development of AAI. Oxidative stress biomarkers were measured in murine sera or lung homogenates. RESULTS: We demonstrate a direct association of dietary sucrose with asthma prevalence in males, while starch was associated with higher asthma prevalence in females. In mice, high-carbohydrate feeding, despite scant metabolic effects, aggravated AAI compared to high-fat in both sexes, as displayed by humoral response, mucus hypersecretion, lung inflammatory cell infiltration and TH 2-TH 17 profiles. Compared to high-fat, high-carbohydrate intake was associated with increased pulmonary oxidative stress, signals of metabolic switch to glycolysis and decreased systemic anti-oxidative capacity. CONCLUSION: High consumption of digestible carbohydrates is associated with an increased prevalence of asthma in humans and aggravated lung allergic inflammation in mice, involving oxidative stress-related mechanisms.
Keywords: Cross-Sectional Studies; škrob; Male; Inflammation; plíce; Adolescent; Dietary Carbohydrates; prevalence; pneumonie; mužské pohlaví; Pneumonia; mladiství; zánět; Lung; Animals; lidé; ženské pohlaví; Humans; zvířata; dietní sacharidy; Prevalence; průřezové studie; myši; Asthma; Starch; sacharosa; Mice; Female; Sucrose; bronchiální astma